Factors Affecting the Physicochemical, Nutritional, and Sensory Quality of Sheep Meat (Ovis aries): A Systematic Review - Modawy Abdelgader Elbasheer Altayb; Tasnim Hunin AbdElwhab Mohamed (Fakultas Peternakan. Unwiku, Purwokerto, 2026)
This review synthesizes evidence on the factors that govern the quality of sheep meat (Ovis aries), a commodity of growing economic and nutritional importance in Indonesia and worldwide. A systematic search of Scopus, ScienceDirect, PubMed, and the Garuda/SINTA index, following PRISMA 2020 guidelines, retrieved peer-reviewed studies published between 2000 and 2025 that reported physicochemical, nutritional, or sensory attributes of sheep meat; 35 studies met the eligibility criteria and were synthesized narratively. The reviewed evidence indicates that meat quality is multidimensional and is shaped by intrinsic factors (breed/genotype, age and slaughter weight, sex) and extrinsic factors (feeding system and diet, pre-slaughter handling, and post-mortem processing). Forage- and pasture-based systems consistently raised n-3 polyunsaturated fatty acids and conjugated linoleic acid, improving the nutritional profile, whereas concentrate finishing increased intramuscular fat and n-6 fatty acids. Slaughter age and weight were the dominant determinants of tenderness, intramuscular fat, and flavor intensity, while post-mortem aging reduced Warner-Bratzler shear force and improved water-holding capacity. Reported Indonesian local-sheep values (Domba Ekor Tipis and Domba Garut) clustered at pH 5.79-6.03, cooking loss 24-25%, and shear force 1.9-2.7 kg cm-2, comparable with international light-lamb data. The principal research gaps are the scarcity of standardized, fatty-acid-resolved studies on Indonesian indigenous breeds and the limited use of objective sensory protocols. Strategic manipulation of breed, slaughter age, diet, and aging is recommended to optimize both the eating and nutritional quality of sheep meat.